Application of an e-learning quality guide with checklists - Alfredo Soeiro (2013)
This paper was produced based on the "Quality Guide of Open and Distance Learning" produced in a project subsidized by the Socrates E-learning European Cooperation Programme. It was written by Alfredo Soeiro (University of Porto, Portugal), Brian Perry (University of Hertfordshire, UK), Steve Bennett (University of Hertfordshire, UK), Jef Van den Branden (LINOV-Katholike Universitat Leuven, Belgium), José Collado Medina (Universidad Nacional de Educacion a Distancia, Spain), Juan Manuel Moreno Olmedilla (Universidad Nacional de Educacion a Distancia, Spain), Samuel Gento Palacios (Universidad Nacional de Educacion a Distancia, Spain), László Komáromi (SZÁMALK Training and Consulting Centre, Hungary) and András Bardócz-Tódor (Centre for Educational Services, Hungary). It is composed by a summarized description of five sequential phases that are described each one by a set of questions organized in checklists. It is a simplified approach with practical and relevant relevance.